2016
DOI: 10.4103/2152-7806.189296
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic brain injury and subsequent glioblastoma development: Review of the literature and case reports

Abstract: Background:Previous reports have proposed an association between traumatic brain injury (TBI) and subsequent glioblastoma (GBM) formation.Methods:We used literature searches and radiographic evidence from two patients to assess the possibility of a link between TBI and GBM.Results:Epidemiological studies are equivocal on a possible link between brain trauma and increased risk of malignant glioma formation. We present two case reports of patients with GBM arising at the site of prior brain injury.Conclusion:The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(68 citation statements)
references
References 56 publications
0
64
0
Order By: Relevance
“…110 Cases of GBM occurring at the site of a prior traumatic brain injury have raised the hypothesis that a reactive astroglial proliferation in conjunction with inflammatory processes may provide the soil for neoplastic transformation, but epidemiologic data are lacking. 111,112 Inherited Factors Genome-wide association studies have identified several genetic loci associated with increased risk of glioma, including TERT, CDKN2A/2B, RTEL1, PHLDB1, EGFR, TP53, TERC, DDX6, and PIWI-interacting RNAs. [113][114][115] Of these genes, TERT, CDKN2A/2B, EGFR, and TP53 are wellcharacterized recurrently altered genes in sporadic IGs.…”
Section: Selected Environmental Factorsmentioning
confidence: 99%
“…110 Cases of GBM occurring at the site of a prior traumatic brain injury have raised the hypothesis that a reactive astroglial proliferation in conjunction with inflammatory processes may provide the soil for neoplastic transformation, but epidemiologic data are lacking. 111,112 Inherited Factors Genome-wide association studies have identified several genetic loci associated with increased risk of glioma, including TERT, CDKN2A/2B, RTEL1, PHLDB1, EGFR, TP53, TERC, DDX6, and PIWI-interacting RNAs. [113][114][115] Of these genes, TERT, CDKN2A/2B, EGFR, and TP53 are wellcharacterized recurrently altered genes in sporadic IGs.…”
Section: Selected Environmental Factorsmentioning
confidence: 99%
“…Trauma-associated gliomagenesis may be explained by TBI-induced inflammation, in turn leading to malignant transformation of neighboring neural progenitor cells. 23 …”
Section: Discussionmentioning
confidence: 99%
“…Multiple brain injuries (a brain injury in infancy followed by another TBI later in life) may be much more likely to produce a primary tumour than a single injury [20]. This may indicate that the severity of the injury may correlate to the risk of developing a tumour as a result of posttraumatic inflammation, stem and progenitor cell transformation [21].Preston-Martin etalfound that head injury resulting in loss of consciousness or a permanent scar increased the risk for brain tumour especially meningiomas in men lending some credence to the connection between brain injury severity and subsequent tumour development [2].…”
Section: Discussionmentioning
confidence: 99%